PROTOTYPE SHEETINGLINE CUT BERBASIS MIKROKONTROLLER AT89S52 DI PT. SURYA ZIG ZAG KEDIRI ( TINJAUAN SECARA SISTEM ) - , NANANG KHABIBUL JINAN, Maun Budiyanto S,T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT.Surya Zig Zag is a manufacture which produces cigarette paper. In the production process, there is a device which the way of working is not automatic yet and still use man power dominantly. The device is used in cigarette paper cutting process and the cigarette paper will be sent to another cigarette manufacturers. Fot that reasons, it need to repair the device focused on automation aspect. The recommended device is prototype based on microcontroller AT89S52 sheetingline cut. The aims of the recommended device are to evaluate the perfomance of current manufactureâs device and to recommend the repaired device as improvement. In the design process, the first step is making block system diagrams to identify the need of inputs and outputs of microcontroller. The next steps are designing mechanical system and positioning the sensor